Perancangan Sistem Informasi Human Capital Management Berbasis Website - Yuni Fitriani; Sri Utami; Bambang Junadi (JISAMAR (Journal of Information System, Applied, Management, Accounting and Research), 2022)
The management of employee data in an organization or company requires a system that is strong and integrated with other parts, and is supported by information technology, which makes the system run smoothly and is interrelated. To support the function of human resources, a Human Capital Management information system is needed for effective and efficient data recording and is easily accessible to employees or management. Where the human capital management information system created is focused on recording employee administration such as employee profile, online attendance and time management. The system development method used in this study is the Waterfall method. The Waterfall method is a sequential or sequential software development process starting at the level and progress of the system at the stage of analysis, design or design of coding, testing and maintenance With the development of the Human Capital Management information system, it is expected to improve employee performance and facilitate operational activities in the human resources department, especially in employee data processing, employee attendance and employee time management.